2003
DOI: 10.1090/s0002-9947-03-03046-0
|View full text |Cite
|
Sign up to set email alerts
|

Quandle cohomology and state-sum invariants of knotted curves and surfaces

Abstract: Abstract. The 2-twist spun trefoil is an example of a sphere that is knotted in 4-dimensional space. A proof is given in this paper that this sphere is distinct from the same sphere with its orientation reversed. Our proof is based on a state-sum invariant for knotted surfaces developed via a cohomology theory of racks and quandles (also known as distributive groupoids).A quandle is a set with a binary operation -the axioms of which model the Reidemeister moves in classical knot theory. Colorings of diagrams o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
456
0
7

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 336 publications
(467 citation statements)
references
References 40 publications
1
456
0
7
Order By: Relevance
“…Lemma 3.20 [Carter et al 1999;2003b]. The state-sum S λ Q is invariant under Reidemeister moves and thus defines a knot invariant S λ Q : → ‫ޚ‬ .…”
Section: Amentioning
confidence: 99%
See 2 more Smart Citations
“…Lemma 3.20 [Carter et al 1999;2003b]. The state-sum S λ Q is invariant under Reidemeister moves and thus defines a knot invariant S λ Q : → ‫ޚ‬ .…”
Section: Amentioning
confidence: 99%
“…Every quandle colouring number F q Q is the specialization of some knot colouring polynomial P x G . Quandle cohomology was initially studied in order to construct invariants in low-dimensional topology: in [Carter et al 1999;2003b] it was shown how a 2-cocycle λ ∈ Z 2 (Q, ) gives rise to a state-sum invariant of knots, S λ Q : → ‫ޚ‬ , which refines the quandle colouring number F Q . We prove the following result: Theorem 1.11 (Section 3E).…”
Section: Put Itmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Joyce [7] shows that the square knot and the granny knot have nonisomorphic knot quandles despite having isomorphic knot groups. 2 In [11] we have the following definition.…”
mentioning
confidence: 99%
“…One way of implementing these ideas is via the CJKLS invariant of knots ( [1,2]). There is a CJKLS invariant for each choice of labeling quandle X , abelian group A, and 2-co-cycle φ in H 2 (X , A).…”
Section: Introductionmentioning
confidence: 99%